PENDETEKSIAN POTENSI CADANGAN KARBON DI ATAS PERMUKAAN PADA HUTAN MANGROVE DI KUBU RAYA MENGGUNAKAN CITRA ALOS PALSAR - Hudaya, Yudi Fatwa; Hartono, Hartono; Murti, Sigit Heru; Hadiyan, Yayan (Institut Teknologi Sepuluh Nopember, 2015)
The need for sufficient forest carbon stock measurement system which encompasses a faster and covering broader geographic area is now growing, one of which is the use of synthetic aperture radar (SAR). The objectives of this study were to demonstrate the advantage of ALOS PALSAR application for carbon quantification in mangroves, which apparently provided better relationship in between the L-band backscatters of ALOS PALSAR and the actual aboveground allometric based forest carbon stock of mangroves, compared with previous studies in other types of forest. i.e in tropics or temperate lowland until mountain forests. The better relationship explained by the coefficient determination (R²) of 62 % based on HH polarization with the equation model of Y = 1647.20 + 6.8288BS_HV + 279.48BS_HV + 2870. While previous studies mentioned the R² were only 16 - 76%. The models obtained subsequently were subjected to total carbon quantification and their distributions were mapped. The quantity of aboveground biomass of mangrove forest in Kubu Raya Regency was (Mega grams) or 5.3 Mt (Mega grams), the quantity of carbon dioxide (CO2) sequestration reached 19 451 Mt (Megagrams) equivalent. The 71,069.21 ha area of mangrove forest has the potential to reduce the rate of GHG (Green House Gas) emissions from forestry sector by 0.76%.